2010
DOI: 10.1016/j.plantsci.2010.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Variability of carotenoid biosynthesis in orange colored Capsicum spp.

Abstract: Pepper, Capsicum spp., is a worldwide crop valued for heat, nutrition, and rich pigment content. Carotenoids, the largest group of plant pigments, function as antioxidants and as vitamin A precursors. The most abundant carotenoids in ripe pepper fruits are β-carotene, capsanthin, and capsorubin. In this study, the carotenoid composition of orange fruited Capsicum lines was defined along with the allelic variability of the biosynthetic enzymes. The carotenoid chemical profiles present in seven orange pepper var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(162 citation statements)
references
References 35 publications
7
150
0
5
Order By: Relevance
“…Marin et al [31] reported a high pro-vitamin A content in the mature stage of peppers. Recently, Guzman et al [11] indicated that orange or yellow color in Capsicum fruit can have very low amounts of the β-carotene level. The level of β-carotene in pepper depends upon various factors: the level of expression of the genes governing carotenogenesis, physiological and morphological characteristics intrinsic to the cultivar, and probably growth conditions [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Marin et al [31] reported a high pro-vitamin A content in the mature stage of peppers. Recently, Guzman et al [11] indicated that orange or yellow color in Capsicum fruit can have very low amounts of the β-carotene level. The level of β-carotene in pepper depends upon various factors: the level of expression of the genes governing carotenogenesis, physiological and morphological characteristics intrinsic to the cultivar, and probably growth conditions [31].…”
Section: Discussionmentioning
confidence: 99%
“…Ha et al [32] observed that beta carotene content in the Capsicum cultivars ranged from 100 to 1300 µg 100g -1 fresh weight. Guzman et al [11] indicated that β-carotene contents could range from 100 µg to 6000 µg 100 g -1 dry weigh. The more recently devised Dietary Reference Intake (DRI), [33] values for vitamin A, established by the Food and Nutrition board of the Institute of Medicine are, 900 and 700 µg RAE/day for adult (ages 19-50 years) males and females, respectively (IOM) [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be because anthocyanin content and carotenoid content are highly influenced by genetics (Ficco et al, 2014;Fournier-Level et al, 2009;Guzman et al, 2010;Nicolle et al, 2004) while chlorophyll content is influenced by both genetics and environmental conditions and stressors (Cao, 2000;Malyshev et al, 2016).…”
Section: Red Trough and Red Edge Regionsmentioning
confidence: 99%